1999
DOI: 10.1128/mcb.19.10.6500
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Receptor Interacting Protein 3 Does Not Contain a Caspase-Recruiting or a Death Domain but Induces Apoptosis and Activates NF-κB

Abstract: The death domain-containing receptor superfamily and their respective downstream mediators control whether or not cells initiate apoptosis or activate NF-kappaB, events critical for proper immune system function. A screen for upstream activators of NF-kappaB identified a novel serine-threonine kinase capable of activating NF-kappaB and inducing apoptosis. Based upon domain organization and sequence similarity, this novel kinase, named mRIP3 (mouse receptor interacting protein 3), appears to be a new RIP family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
43
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 54 publications
6
43
2
Order By: Relevance
“…5A) and cell death ELISA (Fig. 5B), consistent with previous studies on other cell types (33)(34)(35)(36). Next, we envisioned that normalizing Akt activation by adenoviral gene transfer of the constitutively active PI3K mutant might protect cells from rRIP3-induced cell death.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…5A) and cell death ELISA (Fig. 5B), consistent with previous studies on other cell types (33)(34)(35)(36). Next, we envisioned that normalizing Akt activation by adenoviral gene transfer of the constitutively active PI3K mutant might protect cells from rRIP3-induced cell death.…”
Section: Resultssupporting
confidence: 77%
“…Previous studies have shown that the kinase activity of RIP3 contributes to its necrotic effect (40), whereas other studies suggest that the kinase activity is not necessary for its apoptotic effect (34). To determine whether the kinase activity is involved in rRIP3-induced growth arrest and apoptosis, we made a kinaseinactive mutant of RIP3 (rRIP3-C, which lacks the kinase domain).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This experiment also proved that RIP3 sensitized MCF-7 and MDA-MB-231 cells to PTL-induced apoptosis. Contrary to the report that RIP3 overexpression could induce apoptosis [19][20][21] , we did not observe any spontaneous apoptosis in our RIP3-MCF-7 or RIP3-MDA-MB-231 cells. This may be because previous work studied apoptosis as soon as 24 h after transient transfection of the RIP3 constructs, while we tested the cells after one-week antibiotic selection.…”
Section: Discussioncontrasting
confidence: 54%
“…6,7 RIPK3, like RIPK1, bears a kinase domain and RIP homology interaction motif (RHIM), but unlike RIPK1 does not have a DD. [8][9][10][11] RIPK3 is required for necroptosis. 12,13 Furthermore, RIPK1 appears to activate RIPK3 in this pathway, as cell death could be blocked by nec-1.…”
mentioning
confidence: 99%